AKIBAT HUKUM TERHADAP DEVELOPER PERUMAHAN YANG TIDAK SEDIAKAN SARANA, PRASANA, UTILITAS BERDASARKAN PERATURAN PEMERINTAH NOMOR 12 TAHUN 2021 TENTANG PENYELENGGARAAN PERUMAHAN DAN KAWASAN PERMUKIMAN - Afriza, Noviedz Zulvan (Universitas 17 Agustus 1945 Samarinda, 2022)
ABSTRACTHousing development in Indonesia is mostly done by developers. The increasing number of developers in the housing sector certainly makes it easier for people to make their choices in choosing a house according to their respective financial capabilities. When the housing is still under construction, housing marketing can be done through a pre-sales purchase agreement (PPJB) system that must include certainty on several things, one of which is the availability of infrastructure, facilities, and public utilities. However, in practice, it will be a problem if there is a discrepancy between what is listed in the brochure or advertisement in the form of product information, with what is contained in the sale and purchase agreement signed by the consumer, especially if there is no availability of infrastructure, facilities, and public utilities. In other words, the developer is in default.The problems raised in this paper are legal consequences for developers who do not provide public infrastructure, facilities, and utilities based on Government Regulation Number 12 of 2021 concerning the Implementation of Housing and Settlement Areas and legal remedies that consumers can take, if the developer defaults.The type of research in this research is normative legal research. The approach method of this research is the approach to legislation (Statue approach). The technique of collecting legal materials used by the authors of the literature study.The results of the study show that the legal consequences for developers who do not provide infrastructure, facilities, and public utilities, developers can be subject to administrative sanctions as stipulated in Article 50 number 15 of Law Number 11 of 2020 concerning Job Creation and the developer concerned can also be charged. criminal offense if it results in victim/damage to health, safety, and/or the environment. Based on Article 50 point 16 of Law Number 11 of 2020 concerning Job Creation.Efforts that can be made by consumers if the developer is negligent of the contents of the PPJB. Consumers in the first step can ask the developer regarding existing problems, after that they can call or reprimand the developer. If there is no response from the developer, they can file a lawsuit to the local district court. Keywords: Legal Consequences, Developer, Infrastructure and Public Utilities